The Relationship between Perceived Alcoholics Anonymous Social Group Dynamics and Getting an AA Sponsor. Issue 1 (2nd January 2020) - O'Sickey, A. J.; Hanes, Jacob; Tonigan, J. Scott
ABSTRACT: Research has shown that aspects of group dynamics of AA meetings are associated with AA attendance, alcohol use, and engagement in prescribed AA behaviors. This study investigated whether perceptions of AA meeting group dynamics changed over 12 months and whether these dynamics predicted the probability that a new member would get a sponsor. Results showed that perceptions of the group dynamics of AA meetings did not change over the 12-month assessment period. Member perception of group cohesion was the only AA meeting group dynamic that predicted a new member getting a sponsor. Findings suggest that group cohesion plays an important role in AA members recovery efforts.